The Synergy between Health Administration and Nursing: Enhancing Patient Care and Operational Efficiency - Shaker Aali Ali Alsuwat,; Nasib Mohamed Sawed Alghamdi,; Alaa Abdullah Sulaimani,; Athari Omar Barnawi,; Fawaz Abdullhameed H Felimban,; Mohammed Saad Ghazi Alsharif,; Riyadh Hamed Alharthi,; Bandar Abdu Hassan Alnami,; Naif Habeb Allah Alsaedi,; Saleh Marzouq Alruwaythi,; Asrar Khalid Alynbawi,; Nouf Mohammed Aboud Anbar,; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
The health administration and nursing go hand in hand in bringing about improvements in patient care and operational efficiency in health systems. The relationship between health administrators and nurses will be reviewed in terms of the need for these two to work together in order to improve patient safety and patient satisfaction. In improving safety culture, analysis, and integrating patient safety concepts into nursing education and practice, both of these work towards bringing in optimal health delivery. Health administrators, by making such policies and systems that ensure safety and efficiency, provide the enabling environment for the nurses to translate these policies into practice on the ground through evidence-based practice and quality care. Workforce development and resource management are several of these challenges that will be discussed along with overcoming the barriers for better outcomes in patients.